Android-Based Quizizz: Media for Students' Learning Motivation and Mastery of Mathematical Concepts - Effendi, Moh. Mahfud; In’am, Akhsanul (International Journal on Emerging Mathematics Education, 2024)
The use of media that suits students' conditions influences their learning motivation and mastery of mathematical concepts. Therefore, teachers must know the learning media that will be used. Quizizz, which is in the form of a quiz and based on 4.0, can be used as a learning medium because it is game and technology based. Therefore, the aim of this research is to describe the effect of using Quizizz on students' learning motivation and mastery of mathematical concepts. The approach used is quantitative through experiments at SMPN 14 Raja Ampat, West Papua. To obtain data on student learning motivation and mastery of mathematical concepts, questionnaires and tests are used. Based on the results of the analysis, it was found that the use of Quizzizz had a significant effect on student learning motivation (the difference is 16.4%) and mastery of mathematical concepts (the difference is 19.04%).